ANALISIS PENGOPERASIAN PADA OPERATOR RUBBER TYRED GANTRY (RTG) di TERMINAL PETI KEMAS SEMARANG - Pribadi, Kevin Yudhistira; Ekawati, Ekawati; Widjasena, Baju (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
In the logistics industry, in the case of heavy equipment accident one of them caused by the behavior of the operators of heavy equipment unsafe. Semarang Container Terminal has a Rubber Tyred Gantry (RTG) for 16 units. Rubber Tyred Gantry crane (RTG crane) is a type of gantry crane used to stack and take the container to the container yard and includes lift equipment which have a high risk. Semarang Container Terminal has a considerable number of operators and also loading-unloading activities are routine, it is very possible for accidents due to operator Rubber Tyred Gantry behavior. This study aimed to analyze the operation of the operator Rubber Tyred Gantry (RTG) in Semarang Container Terminal. This research is a descriptive qualitative in-depth interviews and observation. The subjects of this study amounted to 10 as key informants and 3 as triangulation informants. The results showed operator RTG have had knowledge of the behavior of safe work in operating RTG appropriate procedures have been defined by the company, operator RTG also have the perception if it should work safe and also had a good attitude at work, operator RTG also coordinate with the tally man who was in under RTG, in coordination with the supervision of the shift and in coordination with other operators during RTG operation, operator RTG own SIO and have training and supported by their supporting facilities related to the operation of the RTG to keep working safe, in addition to the operator RTG also agreed to the rules reward and punishment of the company as a consequence of the behavior of the operator. The conclusion of this study is the behavior of operator to appropriate RTG operation procedures. But still there are some operators that have not been orderly and often miss communication during operation of the tool. Companies need to provide stricter oversight if there are employees both operator and non-operator if any disciplinary breaches in the field and also need to improve the supporting facilities.